Sosialisasi Penggunaan Aplikasi Literasi Digital Dalam Bentuk Prototyping di Desa Bulu Cina - Virdyra Tasril; Muhammad Iqbal; Adinda Silvana Dewi; Endicha Eklis Syahputra; Anwar Suhut (JPM: Jurnal Pengabdian Masyarakat, 2023)
This activity aims to improve children's understanding and digital literacy skills through an innovative approach called "Literacy Corner". In the era of modern technology, the ability to understand and use digital tools is an essential skill. This research was conducted at the Bulu Cina Village office hall, where the PKM Team collaborated with partners, namely the Gugah Nurani Indonesia Foundation, to develop the potential of the community in Bulu Cina Village. This research implemented a digital literacy socialization program at the children's literacy corner with a focus on strengthening the skills of reading, writing, and understanding digital content. The methods used included interactive workshops, small group discussions and practical activities. The materials presented included an introduction to various digital platforms, the use of search tools and the importance of digital criticism in consuming online information. In addition, this program also emphasizes aspects of online safety and digital ethics. The method of this socialization activity involves lecturers, the GNI team, and students in its implementation. The results of this socialization showed that out of 30 children who could understand the meaning of digital literacy, only about 78.93% understood.